Perilaku Bullying terhadap Self-Esteem Remaja - Nabila Hanifatus Zahra (Pusat riset dan Inovasi Nasional, 2025)
This study aims to analyze the phenomenon of bullying through a literature review approach that relies on various relevant sources of information. The method used in this research is a literature review, which involves gathering, evaluating, and analyzing literature related to bullying and its impact on adolescent self-esteem. The sources used include scholarly articles, journals, books, and previously published publications. In this process, the researcher analyzes literature regarding the factors influencing bullying, its impact on adolescent psychological development, and the relationship between bullying and self-esteem. This study also identifies key findings and gaps in the existing literature. The analysis results show that bullying significantly affects the decrease in adolescent self-esteem, and there is an inverse relationship between the two. This study recommends the need for more focused prevention efforts on the root causes of bullying, as well as the necessity of social support for both victims and perpetrators of bullying to reduce the negative impact on adolescent psychological development.